Women's voices in a deliberative assembly: An analysis of gender rates of participation in Ireland's Convention on the Constitution 2012–2014. (February 2021) - Harris, Clodagh; Farrell, David M; Suiter, Jane; Brennan, Mary
Ireland's Convention on the Constitution (2012–2014) was a world-first process in mixing randomly selected private citizens and political representatives in a deliberative mini-public that made recommendations on a wide range of constitutional issues. Acknowledging the gender gap identified in studies of deliberative forums, the Convention made specific design choices in an effort to achieve gender inclusion. Using data collected during the course of the Convention, we explore the effects of contextual (institutional rules, procedures and topics discussed) and actor-related characteristics (gender, type of membership) on inclusion. We find that contextual issues such as the topic discussed and the gender composition of the small roundtable deliberations did not influence gender rates of participation. However, the forum of participation did, with women participating more than men in the facilitated small group sessions.